Implementation of the full‑day school model to enhance akidah akhlak instruction at Madrasah Aliyah Negeri 2 Surakarta - Solekhah Nur Afifah; Meti Fatimah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study investigates how a Full‑Day School (FDS) model improves learning outcomes in the Islamic Creed and Morals (Akidah Akhlak) subject at MAN 2 Surakarta. Using a qualitative single‑case/ethnographic design, data were gathered from school leaders, the vice‑principal for curriculum, Akidah Akhlak teachers, and students through participant observation, semi‑structured interviews, and document analysis (lesson plans, schedules, portfolios). Data were analysed using the Miles–Huberman framework, with credibility ensured through triangulation, member checking, and an audit trail. The findings indicate that FDS converts extended school hours into high‑quality learning experiences through an integrated curriculum and daily religious routines, diversified pedagogies, and multi‑domain formative and summative assessment. Positive impacts emerge in the cognitive (concept mastery and theological reasoning), affective (habituated worship and manners), and psychomotor (worship and recitation skills) domains. The magnitude of these impacts is moderated by facilities readiness, humane time management, and teachers’ pedagogical competence. Practical implications include block scheduling, structured repertoires of methods, three‑domain rubrics, and sustained teacher development; future research should incorporate longitudinal quantitative measures.